The Relationship Between Work Motivation and Work Discipline With Teacher Performance In State Junior High Schools in Baguala District, Ambon City - Coni Taihuttu; Tanwey Gerson Ratumanan; Lamberthus J. Lokollo (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine the relationship between work motivation and work discipline with teacher performance. This research was conducted at SMP Negeri Baguala District, Ambon City, involving 123 teachers. The research results explained that for the data description obtained work motivation in this study 107 teachers (86.99%) had high work motivation and 16 teachers (13.01%) had moderate work motivation. Work discipline was obtained by 43 teachers (34.95%) having very high work discipline, 78 teachers (63.42%) had moderate work discipline and 2 teachers (1.63%) had low work discipline. Furthermore, for teacher performance, it was found that 41 teachers (33.33%) had very high teacher performance, 77 teachers (62.60%) had moderate teacher performance and 5 teachers (4.07%) had low teacher performance. Based on the results of the analysis of the three hypotheses, the following conclusions can be obtained (1) There is a positive and significant relationship between work motivation and teacher performance, this is evidenced by the r count of 0.414 with the price tcount 5.002 > from ttable 1,979. (2) There is a positive and significant relationship between work discipline and teacher performance. this is proved rcount 0.531 at the price tcount 6,891 > from ttable 1.979, this means. (3) there is a positive and significant relationship between work motivation and work discipline together with teacher performance, this is evidenced from R 0.557 with a priceFcount27.019 > from Ftable 3,07.